Reversible solid-oxide cells for clean and sustainable energy. Issue 3 (5th October 2019) - Mogensen, M B; Chen, M; Frandsen, H L; Graves, C; Hansen, J B; Hansen, K V; Hauch, A; Jacobsen, T; Jensen, S H; Skafte, T L; Sun, X
Abstract: This review gives first a brief view of the potential availability of sustainable energy. It is clear that over 100 times more solar photovoltaic energy than necessary is readily accessible and that practically available wind alone may deliver sufficient energy supply to the world. Due to the intermittency of these sources, effective and inexpensive energy-conversion and storage technology is needed. Motivation for the possible electrolysis application of reversible solid-oxide cells (RSOCs), including a comparison of power-to-fuel/fuel-to-power to other energy-conversion and storage technologies is presented. RSOC electrochemistry and chemistry of H2 O, CO2, H2, CO, Cn Hm (hydrocarbons) and NH3, including thermodynamics and cell performance, are described. The mechanical strength of popular cell supports is outlined, and newly found stronger materials are mentioned. Common cell-degradation mechanisms, including the effect of common impurities in gases and materials (such as S and Si), plus the deleterious effects of carbon deposition in the fuel electrode are described followed by explanations of how to avoid or ease the consequences. Visions of how RSOCs powered by sustainable energy may be applied on a large scale for the transportation sector via power-to-fuel technology and for integration with the electrical grid together with seasonal storage are presented. Finally, a brief comparison of RSOCs to other electrolysis cells and an outlook with examples of actions necessary to commercialize RSOC applications are sketched.